Liquidity hoarding - Douglas Gale; Tanja Yorulmazer (Federal Reserve Bank of New York, 2011)
Banks hold liquid and illiquid assets. An illiquid bank that receives a liquidity shock sells assets to liquid banks in exchange for cash. We characterize the constrained efficient allocation as the solution to a planner's problem and show that the market equilibrium is constrained inefficient, with too little liquidity and inefficient hoarding. Our model features a precautionary as well as a speculative motive for hoarding liquidity, but the inefficiency of liquidity provision can be traced to the incompleteness of markets (due to private information) and the increased price volatility that results from trading assets for cash.
Keywords: G12; G21; G24; G32; G33; D8; 330; interbank market; fire sale; Bankenliquidität; Bankgeschäft; Geldmarkt; Theorie